Análise geoecológica como subsídio ao planejamento ambiental da bacia hidrográficado rio Caldas-GO - Sousa, Ana Caroline Rodrigues Cassiano de (2021)
The landscapes of hydrographic basins in Cerrado of Goiás are the target of many transformations, often due to agriculture and pasture exploitation and due to the lack of the use planning of natural resources, which can cause environmental impacts as vegetation fragmentation and erosions, which motivate integrated and interdisciplinary studies, as that utilized in the theoretical and methodological approach of Landscape Geoecology. The Hydrographic Basin of Caldas River (BHRC) presents multiple uses and its main river is indicated as the future watercourse for the public supply of the Metropolitan Region of Goiânia. Therefore, this work aims to propose priority areas for environmental conservation of BHRC, to reduce the impacts of fragmentation and soil losses. The methodological procedures involved the surveying of the socio-environmental aspects; the cartography of Geoecological Unities (UGs) by superposition of hypsometry, slope, precipitation, geology, and pedology; the analysis of land occupation dynamics through MapBiomas 4.0 for the years of 1988, 2000 e 2018; the analysis of landscape metrics (CA, PLAND, NP, TCA, TCAI, TE e ENN-MN), validated by Principal Component Analysis; the mapping of erosion vulnerability, with weights and arithmetical standard between the themes; and the adoption of criteria to the proposition of priority areas: remanent areas since 1988, >100ha nearby APPs of water bodies, in UGs more significant and with patches more vulnerable to erosions. The BHRC was compartmentalized into six Relief Geoecological Unities (UGR), subdivided into 34 UGs, and pasture is the predominant class of use in the whole basin. In almost all the UGRs, parts of native vegetation were converted to agriculture and pasture, mainly in soft relief, the grassland area the most fragmented in size and isolation, followed by savannas and forestall, and central areas represents about 21%, 24%, and 45%, respectively; forest isolation and area reduction are considerable, in comparison to other regions of Cerrado. The medium erosion vulnerabilities are predominant since 2000 and the medium and high presents an increase mainly related to anthropogenic uses, which emphasizes the need for conservation to avoid and mitigate risks. Of the remanent fragments since 1988, 19 matched the adopted criteria and were suggested as priority areas to environmental conservation; is expected that this area would be used as aids in the conservation planning of biodiversity, hydric and edaphic protection in BHRC.